Preliminary design optimization of a fully superconducting motor based on disk-up-down-assembly magnets. (1st May 2023) - Wang, Rui; Liu, Yingzhen; Cao, Jiwei; Li, Liyi; Liu, Xiaokun; Xue, Haida; Arndt, Tabea
Abstract: The transition to electric propulsion for aircraft provides an effective way to reduce fuel consumption and achieves low-carbon aviation. Due to the advantages of high magnetic field and ultra-compactness of superconducting disk-up-down-assembly ('DUDA') magnets, they have a promising use in superconducting motors. Therefore, this paper presents a design of a fully superconducting motor using superconducting DUDA magnets with Halbach arrays. In order to study the feasibility of the superconducting DUDA magnets in electric motors, preliminary studies of two sets of 4-layer superconducting DUDA magnets were carried out. The manufacturing method with lap joints of the DUDA magnets was proposed and then the manufactured magnets were tested in liquid nitrogen. The contact resistance and critical current at each lap joint have been calculated and the magnetic field distribution of the magnets has been measured. The magnetic fields of the magnets were also verified by simulation and then the magnets were scaled up in size to meet the magnetic field magnitude for the motor. It has been proved that the DUDA magnets can generate a constant magnetic field above 1.11 T along the x -axis without iron materials, which meets the requirements of motors. Based on the analysis of electromagnetic performance, the structural parameters of the superconducting DUDA magnets were optimized with different pole-slot number combination in order to obtain higher efficiency and specific power density. To calculate the efficiency, finite element models in Comsol evaluated the AC losses of the superconducting DUDA magnets. By changing the slot type and winding configuration, the optimized motor is able to achieve a specific power density of 11.55 kW kg −1 with an efficiency of 98% at 30 K.